Effect of processing, packaging and storage conditions. on bacteria and yeast load of anardana (Indian Journal of Arid Horticulture, 2025)
Anardana is mostly used as an acidulent for most of the Indian curries as it impart special taste, flavour and aroma. In traditional Indian system, the pulp-coated arils of pomegranate are dried in the open space and hence dust, dirt and microorganisms deposit over them. The improper packing in gunny bags results in moisture ingress and caking of product causing chemical and microbial colonization in anardana. Hence, in present experiment drying and dehydration of Bassein Seedless genotype of pomegranate under different conditions along with selection of suitable packaging material was done to reduce the microbial population and make the product hygienic. Steam blanching (with and without sulphuring) prior to drying, in a cabinet drier gave excellent quality of anardana with attractive red colour, firm texture, soft, free flowing with minimum microbial population. Microbial population was not detected in anardana exposed to blanching (with and without sulphuring) before drying in a cabinet drier and hence steam blanching before drying was recommended for preparation of anardana. From the storage studies, it was found that anardana dried under cabinet drier could be safely stored in aluminium pouches and plastic bottles (50% transparent) at low temperature for a period of six months.
Keywords: anardana; pre-treatments; microbes; drying; packing; storage